2014
DOI: 10.1364/ol.39.002790
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory x-ray fluorescence tomography for high-resolution nanoparticle bio-imaging

Abstract: We demonstrate that nanoparticle x-ray fluorescence computed tomography in mouse-sized objects can be performed with very high spatial resolution at acceptable dose and exposure times with a compact laboratory system. The method relies on the combination of the 24 keV line-emission from a high-brightness liquid-metal-jet x-ray source, pencil-beam-forming x-ray optics, photon-counting energy-dispersive detection, and carefully matched (Mo) nanoparticles. Phantom experiments and simulations show that the arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…Afterwards the AuNPs provide the spectrophotometric detection of mecA gene employing their aggregation in the presence of NaCl . For our experiments, we characterized our fabricated AuMNPs, AuNPs, as well as AuNPs in NaCl presence from the point of view of surface analysis , electrochemical properties of particles , qualitative analysis , and measurement of size and zeta potential .…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards the AuNPs provide the spectrophotometric detection of mecA gene employing their aggregation in the presence of NaCl . For our experiments, we characterized our fabricated AuMNPs, AuNPs, as well as AuNPs in NaCl presence from the point of view of surface analysis , electrochemical properties of particles , qualitative analysis , and measurement of size and zeta potential .…”
Section: Resultsmentioning
confidence: 99%
“…The room temperature-implanted nanowires presented a higher structural disorder around Co atoms compared with the high temperature-implanted ones. Hertz et al 406 used laboratory XRF-CT for high spatial resolution NP bio-imaging. The authors simulated and investigated experimentally the sputter yield of ZnO and GaAs nanowires, which were implanted with energetic Mn ions at room temperature.…”
Section: Thin Lms Coatings and Nanomaterialsmentioning
confidence: 99%
“…By detecting the characteristic Kα X-rays emitted from the contrast agents, in vivo spatial distribution and elemental analysis can be achieved under post-imaging reconstruction. With the laboratory XFCT setup Larsson et al reported the 3D imaging of MoO 2 nanoparticles (NPs) in rodents with 200 µm spatial resolution at acceptable X-Ray radiation dose and exposure time with XFCT setup [1,2]. This extends the application of X-Ray CT imaging from structural imaging to molecular imaging Clinically used molecular imaging modalities include magnetic resonance imaging (MRI), optical fluorescence, ultrasound, positron emission tomography (PET) and single-photon emission computed tomography (SPECT) [3].…”
Section: Introductionmentioning
confidence: 99%